Gemstone identification using fluorescence technique / Wan Aizuddin Wan Razali … [et al.] - Wan Razali, Wan Aizuddin; Baharudeen, Nur ’Atiqah; Mat Rawi, Fatin Najihah; Othman, Muhammad Firdaus; Muhamad Ridzwan, Hendrie Johann; Senawi, Syamsyir Akmal; Mohamed, Ruziana (Universiti Teknologi MARA Cawangan Pahang, 2020)
Fluorescence is the emission of light by a substance that absorbs light or other electromagnetic radiation. To date, fluorescence is useful in separating genuine and artificial gemstones. In this study, multiple excitation sources, namely blue, green, red lasers, and white lamp were used to illuminate several samples to produce fluorescence. The samples used were genuine ruby crystal, fake ruby crystal and two dye solutions. The fluorescence signal was then detected using a spectrometer. From spectroscopic analysis, each sample gave a different spectrum and the corresponding wavelength was identified through its peak. The analysis showed that the spectrum peak of genuine ruby crystal was at 694.32 nm, whereas the spectrum peak of fake ruby was at 807.72 nm. This study successfully demonstrated the use of the fluorescence technique to distinguish genuine ruby crystal from its artificial. A similar technique can also be used to identify other gemstones.